NILAI-NILAI LUHUR ARSITEKTUR RUMAH ADAT “TONGKONAN” TORAJA - Danang Wahju Utomo (WalennaE, 2001)
Architecture has its own styte, varieties and culture (symbols) which reflected age and area. Tongkonan architecture style reflected the nature and social organization of Toraja people and traditional house functions. In Tongkonan, we could see the noble values audits personality. Torujkonan is the symbol of Torajanese life which reflected in their behaviors, manners, rules in this world and within their souls.